QUALITY DIFFERENCES OF BOER LIQUID SEMEN DURING STORAGE WITH ADDITION SWEETORANGEESSENTIAL OIL IN TRIS YOLK AND GENTAMICIN EXTENDER - Sitepu, Sukma Aditya; Udin, Zaituni; Jaswandi, Jaswandi; Hendri, Hendri (Journal of Community Research and Service, 2017)
AbstractThe purpose of this study was to know the quality of Boer liquid semen during storage by adding sweet orange essential oil and gentamicin into the tris yolkextender.The semenlongevity test was carried out by storing semen in a closed tube at room temperature and refrigerator, and evaluated motility and Viability every 3 hours at room temperature and 12 hours in refrigerator. The results showed that the characteristics of the liquid semen, with the addition of 1% of essential oils showed percentage of motility and Viability significantly higher than 0.5% and without the addition of essential oil, either stored at room temperature or in the refrigerator. This may be related to the content of essential oils of sweet orange peel containing flavonoids and antibacterials that are capable of maintaining liquid semen quality of Boer Goat.In addition, gentamicin contains antibacterials capable of suppressing the growth of bacteria which can damage and durabilitythe spermatozoa.Keywords: Boer Goat,Gentamicin, Liquid semen, Sweet orange